Substantiation of the composition of concepts for fuzzy cognitive modeling of food security level in the context of import substitution - Rogachev, A (IOP conference series. Earth and environmental science, 2021)
In the national security system of the Russian Federation, food security (FS) is also one of the important tasks, since without a reliable food supply, it is impossible to avoid dependence on other States. Decree of the President of the Russian Federation No. 20 of January 21, 2020 “On the Approval of the Food Security Doctrine of the Russian Federation” approved a new FS Doctrine. The doctrine considers the FS as a multi-component system that includes, as components, the availability of food, its economic, social and physical availability, stability over a long period of time, as well as food issues. To provide cognitive modeling, we can represent the FS support system as a weighted directed graph, whose points correspond to the elements of the set, and whose arcs correspond to the non-zero elements of the W relation. The ratio W can be represented as a matrix of dimension n*n, where n is the number of factors, which can be considered as the adjacency matrix of the graph. The dynamics of the evolution of the simulated socio-economic system and the forecast of its development were obtained by summing increments. The components of the vector of predicted increments of the FCM calculated using the adjacency matrix are calculated at consecutive points in time. It is shown that the following concepts should be taken as key concepts in cognitive modeling of the level of FS: production, consumption, stocks and imports of food, as well as a number of additional ones that characterize the ecological and economic infrastructure for ensuring PB. Modeling has shown that the fluctuating nature of changes in the indicators of all concepts during the transition period forms 3 groups: increasing (FS level, Production, Crop production), stagnating (Consumption) and falling indicators (Import, Irrigation reclamation, Economy, Ecology). The identified trends in the evolution of the main concepts of the level of food security in the context of import substitution should be taken into account when developing programs to ensure FS by subjects of various levels.